2017
DOI: 10.1111/jop.12610
|View full text |Cite
|
Sign up to set email alerts
|

Genetic study of the BRAF gene reveals new variants and high frequency of the V600E mutation among Iranian ameloblastoma patients

Abstract: Background Ameloblastoma is a benign, slow‐growing and locally invasive tumor. It is one of the most prevalent odontogenic tumors, with an incidence rate of 1% of all oral tumors and approximately 18% of odontogenic tumors. A group of genes have been investigated in patients with ameloblastoma. The BRAF V600E mutation has been implicated as the most common mutation in ameloblastoma. The presence or absence of this mutation has been associated with several clinicopathological properties, including location, age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 27 publications
1
25
2
Order By: Relevance
“…As summarized in Table , associations of BRAF V600E mutations in ameloblastoma with clinicopathological factors have been analyzed in previous works . Consistent with previous findings, BRAF V600E mutation status was not associated with sex or histologic patterns in this study. In contrast, discordant results have been reported with regard to other clinicopathological factors in previous and current studies.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…As summarized in Table , associations of BRAF V600E mutations in ameloblastoma with clinicopathological factors have been analyzed in previous works . Consistent with previous findings, BRAF V600E mutation status was not associated with sex or histologic patterns in this study. In contrast, discordant results have been reported with regard to other clinicopathological factors in previous and current studies.…”
Section: Discussionsupporting
confidence: 91%
“…The BRAF V600E mutation was identified in 27 of the 30 ameloblastoma patients by Sanger sequencing (Table ), and other variants, except for p.V600E (c.1799T>A), were not detected in exon 15 of the BRAF gene (Figure A and B). The prevalence of BRAF V600E mutations observed in this study (90.0%) was higher than any other BRAF V600E mutation rate previously reported in patients with ameloblastoma (range, 42.9%‐82.4%; mean, 62.4%; Table ) . Of 27 immunohistochemically stained sections, 17 cases were positive for BRAF V600E (Figure C) and 10 cases showed negative staining including seven false‐negative cases (Figure D).…”
Section: Resultscontrasting
confidence: 54%
See 2 more Smart Citations
“…[17][18][19] Maryam reported a BRAF mutation rate of 63.2% among Iranian AM patients, and the mutation rate was not significantly influenced by tumor distribution, type, mean age, and the genomic location of the mutation. 20 without BRAF V600E mutations were associated with an increased rate of local recurrence. 22 A brief overview of the positive IHC results of BRAF-V600E in AM is presented in Table 2, and the results suggested that VE1 IHC performed on undecalcified tissue sections may be a valid surrogate for BRAF V600E genetic testing.…”
mentioning
confidence: 95%